Association between DNA-repair polymorphisms and survival in pancreatic cancer patients treated with combination chemotherapy. (December 2011) - Giovannetti, Elisa; Pacetti, Paola; Reni, Michele; Leon, Leticia G; Mambrini, Andrea; Vasile, Enrico; Ghidini, Michele; Funel, Niccola; Lucchesi, Matteo; Cereda, Stefano; Peters, Godefridus J; Cantore, Maurizio
Aim: This multicenter study evaluated the association of 11 candidate polymorphisms in eight genes with outcome of pancreatic cancer patients treated with the equivalent polychemotherapeutic regimens: cisplatin/epirubicin/capecitabine/gemcitabine, cisplatin/docetaxel/capecitabine/gemcitabine and gemcitabine/capecitabine plus epirubicin/cisplatin intra-arterial infusion.Patients & methods: Towards this end, polymorphisms were assessed in DNA from 122 pancreatic cancer stage-III/IV patients, and their associations with toxicity/response and progression-free survival (PFS) and overall survival were evaluated using Pearson-χ 2 and log-rank test.Results: Patients harboring XPD Gln751Gln, XPD Asp312Asn + Asn312Asn or XRCC1 Arg399Gln + Gln399Gln genotypes had a worse prognosis. XPD Gln751Gln (hazard ratio: 1.9; p = 0.003), as well as a combination of over two risk genotypes (hazard ratio: 2.7; p < 0.001), emerged as independent predictors for death risk at multivariate analysis. No correlations were observed with toxicity. Conversely, XPD Gln751Gln was associated with shorter PFS, while the lack of association with overall survival/PFS in gemcitabine monotherapy-treated patients suggested its role only for platinum-based regimens.Conclusion: Polymorphisms of DNA-repair genes appear to be candidate biomarkers of primary resistance to gemcitabine/cisplatin-based polychemotherapeutic regimens. The relatively small sample size, coupled with the retrospective and exploratory design of the present study, imply that these results should be considered as hypothesis generators, and should be further evaluated in larger and adequately designed retrospective/prospective studies. Original submitted 26 April 2011; Revision submitted 20 July 2011